Production of cellulose nano-crystals from bacterial fermentation - Pa'e, Norhayati (2019)
The increasing studies of cellulose nano-crystals (CNCs) have proven its growing interest and demand to our society nowadays. However, the major production of CNCs from plant cellulose (PC) is considered less practical due to consuming more energy, time and cost in the purification process. Therefore, an optimum yield of CNCs from bacterial cellulose (BC) is a good alternative to fulfil the need. This study intended to investigate the optimum production of bacterial cellulose nano-crystals (BCNC) through phosphoric acid hydrolysis using One Factor at Time (OFAT) approach and compare its characteristics with plant cellulose. Acetobacter xylinum was incubated in Hestrin Schramm medium at 30°C and pH 6 in static culture. Chemical pre-treatment using sodium hydroxide was done later to prepare CNCs. The optimal conditions for phosphoric acid hydrolysis were BC: acid ratio of 100:1 at 35°C for 60mins. The characteristics and properties of BCNC were investigated and compared with PCNC produced from the same conditions. The result showed that the water holding capacity of BCNC was 5.31g water/g sample which was doubled of PCNC. Fourier-Transform Infra-Red analysis examined the absorption peaks of BCNC were at 1640cm-1 and 3400cm-1 which were similar to PCNC. Yet the crystallinity ratio of BCNC was comparable with PCNC at 0.78. Thermogravimetric analysis showed the degradation temperature of BCNC was 320.43°C, much higher than PCNC that degraded at 163.63°C. Observation from derivative thermo-gravimetric curves showed the ash content of BCNC was approximately 1.6% lower than PCNC, showing that BCNC exhibited much more purity than PCNC. It can be concluded that the behavior of BCNC was similar or even better than PCNC thus it was more advantageous to produce CNCs from bacterial fermentation rather than exploiting the plant source.